Nature-like as agro-technologies a convergent approach to carbon polygon creation - Sevryugina Nadezhda S.; Kozenkova G.L.; Migda N.S. (BIO Web of Conferences)
In this paper, research and validation of nature-like agro-technologies using a convergent approach to improve the productivity of agrolandscapes and the creation of carbon polygons were carried out. As part of the work, a set of experimental studies was implemented, including assessment of agrolandscape potential, comparative analysis of traditional and nature-like farming methods, as well as monitoring of plant physiological parameters and the dynamics of carbon accumulation in the soil. The results of the research showed that nature-like agro-technologies provide a significant increase in yields and quality of grain crops, as well as improve soil fertility and its ability to sequester carbon. At the same time, the cost of production is reduced due to more rational use of natural resources. The obtained data indicate the promising application of nature-based agro-technologies to ensure sustainable and environmentally safe agriculture and to solve the problem of decarbonisation in the agricultural sector.